Pendidik dalam Perspektif Pendidikan Islam - Khoirul Anam; Amri Amri (STAIN Bengkalis, 2020)
Educators are expected to be role models for their students, educators are not only good at having good language delivery skills but also must have an ethic that should be used as uswah, because today not a few educators have poor criteria. As an educator can not only be skilled in conveying something but his heart and actions are worthless. Rasulullah shallallahu ʻalaihi wasallam as a true teacher who once existed in the world taught us. In his hadith that we memorize, he asserted that the prophetic mission of Muhammad is to perfect noble morals. This noble morality is in fact the orientation of all human beings as teachers as an educator.